Penerapan Metode Pembelajaran di Perguruan Tinggi untuk Menghadapi Revolusi Industri 4.0 - Ni’mah Lailatul Mas’adah (Bidayatuna, 2019)
The industrial revolution 4.0 is marked by physical cyber which is starting to be applied in various industries today by developing a virtual world, in the form of human, machine and data connectivity which is better known as the Internet of Things (IoT). This is a form of industrial revolution 4.0 that requires preparation including learning methods for higher education appropriately. Learning methods that require attention to become a symbol of competition for the industrial revolution 4.0, including the development of Human Resources, educational learning methods, information and communication technology for learning in the era of the industrial revolution 4.0. Methods that are deemed appropriate to be applied in the 4.0 industrial revolution, include (1) education held on the basis of the spirit of discovery, (2) education held in the spirit of assembling thinking, or education organized to institutionalize the "assembler" way of thinking (3) to call in successful market players and industrialists known as practitioners or activists in the business and industrial world, make them lecturers, regardless of their academic title, (4) the education that is held must be developed in studies not based solely on scientific disciplines but based on market needs.